Proceeding of Fourth International Conference on Spoken Language Processing. ICSLP '96
DOI: 10.1109/icslp.1996.607326
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic correlates to the effects of talker variability on the perception of English /r/ and /l/ by Japanese listeners

Abstract: It is often reported that for non-native listeners of a language, some native speakers' productions of non-native contrasts are easier to understand than others' (e.g., [1]). However, these effects are not well-understood, as acoustic correlates to the effects have proven difficult to establish. We report analyses of subject differences and acoustic measurements which may help to describe the acoustic phenomena underlying one class of talker effects that we have reported previously; specifically, the interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The more interference which exists between L1 and L2, the less likely phonetic features of the L2 will be produced accurately. There have been many acoustic and perceptual studies examining the effects of various Asian languages on the phonetic features of English spoken as L2 ͑Flege, 1989;Flege and Davidian, 1985;Hutchinson, 1973;Ingram and Park, 1997;Ingram and Pittam, 1987;Kim, 1972;Magnuson and Akahane-Yamada, 1996;Pittam and Ingram, 1992;Robson, 1982;Tarone, 1980͒. The magnitude of phonetic inaccuracies appears to be correlated to the amount of experience ͑or length of time͒ speaking English, or the age period during which L2 was acquired ͑Flege, 1995; Guion et al, 2000;Johnson and Newport, 1991͒.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The more interference which exists between L1 and L2, the less likely phonetic features of the L2 will be produced accurately. There have been many acoustic and perceptual studies examining the effects of various Asian languages on the phonetic features of English spoken as L2 ͑Flege, 1989;Flege and Davidian, 1985;Hutchinson, 1973;Ingram and Park, 1997;Ingram and Pittam, 1987;Kim, 1972;Magnuson and Akahane-Yamada, 1996;Pittam and Ingram, 1992;Robson, 1982;Tarone, 1980͒. The magnitude of phonetic inaccuracies appears to be correlated to the amount of experience ͑or length of time͒ speaking English, or the age period during which L2 was acquired ͑Flege, 1995; Guion et al, 2000;Johnson and Newport, 1991͒.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of phonetic inaccuracies appears to be correlated to the amount of experience ͑or length of time͒ speaking English, or the age period during which L2 was acquired ͑Flege, 1995; Guion et al, 2000;Johnson and Newport, 1991͒. It is believed that after a ''critical period,'' L2 learners have difficulty not only accurately articulating L2 segments ͑Flege, 1987;Lennenberg, 1967;Magnuson and Akahane-Yamada, 1996;Pittam and Ingram, 1992͒, but also in acquiring the suprasegmental features of L2 ͑Chun, 1982;Guion et al, 2000;Guzma, 1973;Scuffil, 1982͒. One aspect of American English noted to be of difficulty for native speakers of tonal languages, specifically East Asian languages, is the production of stress placed on syllables or words ͑Cheng, 1968͑Cheng, , 1987Chun, 1982͒. Wijk ͑1966͒ noted over 30 years ago that correct stressing of words presents a major difficulty in the pronunciation of English for individuals who learn English as L2.…”
Section: Introductionmentioning
confidence: 99%
“…Magnuson and his colleagues obtain similar results in experiments targeting the role of talker variability in non-native phoneme training, i.e. English /r/ and /l/ for Japanese adults (Magnuson, Yamada, Tohkura, Pisoni, Lively & Bradlow 1995;Magnuson & Yamada 1996). Their conclusion is as follows (Magnuson, Yamada, Tohkura, Pisoni, Lively & Bradlow 1995: 394): "while multiple-talker training leads to consistently good results, training with stimuli produced by only one talker may fail to promote generalization to new stimuli and talkers".…”
Section: Training Japanese Listeners To Identify English /R/ and /L/:mentioning
confidence: 65%
“…In their study, listeners expecting to hear a single talker did not show performance costs in word recognition when listeners were expecting to hear two talkers, even though the acoustic tokens were identical. Related work by Magnuson et al (1995) showed that this performance cost is still observed when shifting between two familiar talkers. This example of contextual tuning illustrates that top-down expectations, which occur outside of statistical learning, can fundamentally change how talker variability is accommodated in word recognition.…”
Section: Reliance On Recent Experience and Expectationsmentioning
confidence: 93%